Generalized classical mechanics and field theory : a geometrical approach of Lagrangian and Hamiltonian formalisms involving higher order derivatives - Leon, Manuel de, 1953- (North-Holland mathematics studies ;, 1985)
The aim of this book is to discuss the present situation of Lagrangian and Hamiltonian formalisms involving higher order derivatives. The achievements of differential geometry in formulating a more modern and powerful treatment of these theories is described and an extensive review of the development of these theories in classical language is also given.